Dissemination Of Dakwah Literacy Among Young People Through Social Media - Abdi Mubarak Syam (International Journal of Cultural and Social Science, 2021)
Literacy is a part that is very closely related to everyday life. Literacy mastery is one of the most important indicators to improve the achievements of the younger generation in achieving success. Literacy can also be said as reading and writing. Not only limited to reading and writing, literacy can also be said as sensitivity to technology, economics, politics and others. Advances in technology also bring us to very rapid changes. Technological advances also have a good impact in the field of religion. Because with the advancement of technology so that the formation of da'wah literacy is now starting to be favored by young people through social media, and this has a positive impact on its users.